From Molecules to Materials: Pathways to Artificial Photosynthesis - Rozhkova, Elena A (Springer, 2015)
This interdisciplinary book focuses on the various aspects transformation of the energy from sunlight into the chemical bonds of a fuel, known as the artificial photosynthesis, and addresses the emergent challenges connected with growing societal demands for clean and sustainable energy technologies. The editors assemble the research of world-recognized experts in the field of both molecular and materials artificial systems for energy production. Contributors cover the full scope of research on photosynthesis and related energy processes.